2018
DOI: 10.1371/journal.pone.0204094
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the public towards halal food and associated animal welfare issues in two countries with predominantly Muslim and non-Muslim populations

Abstract: Halal food is that which is permissible or lawful for Muslims to consume. Meat products must abide by a number of requirements in relation to their preparation, condition and content to be considered halal. We conducted a survey in order to assess the knowledge of, and attitudes towards, halal meat products in two contrasting countries, one with a majority non-Muslim population (Australia, respondent n = 565), where the most commonly followed religion is Christianity, and one with a majority Muslim population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…A similar lack of understanding of the facts and requirements for halal slaughter was also found in the UK amongst veterinary students, a group that we might expect to be well-informed [101]. Australians were also likely to believe that Imams must approve all halal meat, and that the slaughterer must completely sever the animal's head, neither of which are required, with the latter being expressly forbidden [11]. The same study also found that the small number of Jewish participants in the study were opposed to the slaughter of conscious animals for religious purposes, despite the fact that stunning is not permitted under shechita.…”
Section: Perception Of the Australian Publicmentioning
confidence: 65%
See 3 more Smart Citations
“…A similar lack of understanding of the facts and requirements for halal slaughter was also found in the UK amongst veterinary students, a group that we might expect to be well-informed [101]. Australians were also likely to believe that Imams must approve all halal meat, and that the slaughterer must completely sever the animal's head, neither of which are required, with the latter being expressly forbidden [11]. The same study also found that the small number of Jewish participants in the study were opposed to the slaughter of conscious animals for religious purposes, despite the fact that stunning is not permitted under shechita.…”
Section: Perception Of the Australian Publicmentioning
confidence: 65%
“…The requirements of kosher and halal slaughter from both religious law, and regulatory perspectives, are poorly understood by most Australians. For example, most halal-certified abattoirs in Australia use reversible stunning, but a 2016 study found that the majority of Australians surveyed believed that stunning is never allowed in halal slaughter [11]. A similar lack of understanding of the facts and requirements for halal slaughter was also found in the UK amongst veterinary students, a group that we might expect to be well-informed [101].…”
Section: Perception Of the Australian Publicmentioning
confidence: 98%
See 2 more Smart Citations
“…The new term of Halal cosmetics was urbanised in recent years, yet some of the Muslims in Islamic countries including Malaysia are still unfamiliar with these Halal cosmetic products as they only recognise the Halal term just for food and beverage products; not for cosmetic and healthcare products. Previous research has been carried out by Ajitha and Sivakumar (2017), Ambali and Bakar (2014), Aziz and Wahab (2013), Jalil et al (2018), and Ruslan et al (2018) on Halal food, but lack of study is focused on Halal cosmetic products which currently catch the purchasers' and manufacturers' attention.…”
Section: Introductionmentioning
confidence: 99%